A functional analysis of the 2012 Finnish Presidential elections. - Paatelainen L; Croucher SM; Benoit W (Redfame Publishing, 2016)
This study applied the functional theory of political campaign discourse, developed for political campaigns in the United States to two televised presidential debates in the 2012 presidential elections in Finland. Acclaims were the most preferred statement by the candidates, with agreements being the least preferred. Policy was discussed more than character during the debates. General goals and ideals were used more frequently to acclaim than to attack. Results are generally consistent with the results of previous studies of presidential elections in the US and other countries. However, differences did emerge: the classical functional categories were supplemented by a new category, the role of the moderator as an attacker in the debate is emphasized, the significance of the diminishing role of the Finnish Presidency is of significance, and the fact that one of the two candidates was the first openly homosexual presidential candidate likely influenced the debates and the election.
Keywords: 2001 Communication and Media Studies